The Educational Philosophy of K.H. Ahmad Dahlan: An Answer to the Crisis of Educational Dualism in the Colonial Era - Athar Abdullatif Husain; Ludfi Robiatul Adawiyah; Muhammad Al Haariz; Rifqi Khairul Anam (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study addresses the 20th-century educational dualism crisis in colonial Indonesia, a pathology split between stagnant religious traditionalism and alienated secular modernity. This article aims to demonstrate that K.H. Ahmad Dahlan's educational philosophy was the valid and coherent epistemological answer to this crisis. Using a qualitative library method and a dialectical-analytical framework, this research diagnoses the pathologies of both poles. The results show that Dahlan’s synthesis—grounded in Tawhid (Divine Unity) as an epistemological unifier and Al-Ma'un praxis as its axiology—is not a mere compromise but a re-foundation. This is proven by demonstrating the fundamental categorical errors within both the traditionalist objection and the modernist-secular objection. The study concludes that this dualism is a the schism of knowledge and that Dahlan's synthesis remains a critical therapeutic model for contemporary education.